2011
DOI: 10.1080/02646838.2011.653961
|View full text |Cite
|
Sign up to set email alerts
|

Infant and maternal factors associated with maternal perceptions of infant sleep problems

Abstract: Aim: Infant sleep behaviours, particularly night wakings, have been identified as one of the most common concerns of parents. Despite this, few empirical studies have examined how mothers distinguish between normative and problematic infant sleep behaviours. Methods: In this study, we examined infant and maternal factors associated with maternal perceptions of infant sleep problems in an internet sample of Canadian mothers with 6-to 12-month-old infants whose infants wake at least one night a week. Results: Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 17 publications
(30 reference statements)
1
11
0
Order By: Relevance
“…Previous research suggests that maternal factors, including depressed mood and poor sleep quality, may bias reports of toddler sleep problems (e.g., Loutzenhiser, Ahlquist, & Hoffman, 2011; Meltzer & Mindell, 2007). However, our results are strengthened by the fact that we controlled for maternal depression and utilized observational measures of child temperament and teacher-reported emotional and behavioral problems.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research suggests that maternal factors, including depressed mood and poor sleep quality, may bias reports of toddler sleep problems (e.g., Loutzenhiser, Ahlquist, & Hoffman, 2011; Meltzer & Mindell, 2007). However, our results are strengthened by the fact that we controlled for maternal depression and utilized observational measures of child temperament and teacher-reported emotional and behavioral problems.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, mothers with histories of sleep problems reported longer infant waking duration and were more likely to identify infant sleep problems. Earlier studies linked poor maternal sleep quality with infant sleep problems (Bayer et al, 2007;Loutzenhiser et al, 2011). We did not collect data on mothers' current sleep problems; however, historical problems may have persisted in this group.…”
Section: Discussionmentioning
confidence: 99%
“…Nightwakings, although shown to be part of normal infant patterns, are often defined as problematic or even “disordered” (Blunden, Thompson, & Dawson, ; Loutzenhiser, Ahlquist, & Hoffman, ; Morgenthaler et al., ; Richman, ; St. James‐Roberts, ). Thus, much of the current research and best practice literature on infant sleep centers on the nature of nightwakings and how to reduce or eliminate them.…”
Section: Are Nightwakings a Problem?mentioning
confidence: 99%